Metabolic Reprogramming of GMP Grade Cord Tissue Derived Mesenchymal Stem Cells Enhances Their Suppressive Potential in GVHD - Mendt, Mayela; Daher, May; Basar, Rafet; Shanley, Mayra; Kumar, Bijender; Wei Inng, Francesca Lim; Acharya, Sunil; Shaim, Hila; Fowlkes, Natalie; Tran, Jamie P.; Gokdemir, Elif; Uprety, Nadima; et al. (Frontiers in Immunology, 2021)
Acute graft-versus-host (GVHD) disease remains a common complication of allogeneic stem cell transplantation with very poor outcomes once the disease becomes steroid refractory. Mesenchymal stem cells (MSCs) represent a promising therapeutic approach for the treatment of GVHD, but so far this strategy has had equivocal clinical efficacy. Therapies using MSCs require optimization taking advantage of the plasticity of these cells in response to different microenvironments. In this study, we aimed to optimize cord blood tissue derived MSCs (CBti MSCs) by priming them using a regimen of inflammatory cytokines. This approach led to their metabolic reprogramming with enhancement of their glycolytic capacity. Metabolically reprogrammed CBti MSCs displayed a boosted immunosuppressive potential, with superior immunomodulatory and homing properties, even after cryopreservation and thawing. Mechanistically, primed CBti MSCs significantly interfered with glycolytic switching and mTOR signaling in T cells, suppressing T cell proliferation and ensuing polarizing towards T regulatory cells. Based on these data, we generated a Good Manufacturing Process (GMP) Laboratory protocol for the production and cryopreservation of primed CBti MSCs for clinical use. Following thawing, these cryopreserved GMP-compliant primed CBti MSCs significantly improved outcomes in a xenogenic mouse model of GVHD. Our data support the concept that metabolic profiling of MSCs can be used as a surrogate for their suppressive potential in conjunction with conventional functional methods to support their therapeutic use in GVHD or other autoimmune disorders.